2019
DOI: 10.1038/s41419-019-1348-0
|View full text |Cite
|
Sign up to set email alerts
|

The long non-coding RNA Linc-GALH promotes hepatocellular carcinoma metastasis via epigenetically regulating Gankyrin

Abstract: Hepatocellular carcinoma (HCC) is the most prevalent subtype of liver cancer, and it is characterized by high rate of metastasis and recurrence. Recent studies have boosted our understanding that Gankyrin contributes to both of these pathological properties, but the mechanisms underlying its aberrant regulation are poorly understood. Recently, many long noncoding RNAs (lncRNAs) have been reported to be involved in regulating the expression of oncogenes and anti-oncogenes through various mechanisms. Here, using… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
25
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(25 citation statements)
references
References 35 publications
0
25
0
Order By: Relevance
“…We found that the transcription factor STAT3, which is recruited by gankyrin, directly binds to the promoter of CCL24 and triggers its transcription in ccRCC. In addition, although some previous studies have shown that the long noncoding RNA Linc-GALH promotes gankyrin/AKT signaling by controlling the methylation status of gankyrin or KIFC1, the upstream regulators should be further studied to determine an effective inhibitor for gankyrin signaling in tumors 32 . Our study found that autocrine CCL24 can trigger the expression and transcription of gankyrin in ccRCC via CCR3, which has not been previously reported.…”
Section: Discussionmentioning
confidence: 99%
“…We found that the transcription factor STAT3, which is recruited by gankyrin, directly binds to the promoter of CCL24 and triggers its transcription in ccRCC. In addition, although some previous studies have shown that the long noncoding RNA Linc-GALH promotes gankyrin/AKT signaling by controlling the methylation status of gankyrin or KIFC1, the upstream regulators should be further studied to determine an effective inhibitor for gankyrin signaling in tumors 32 . Our study found that autocrine CCL24 can trigger the expression and transcription of gankyrin in ccRCC via CCR3, which has not been previously reported.…”
Section: Discussionmentioning
confidence: 99%
“…lncRNA GAS5 functions as a tumor suppressor in HCC metastasis through directly interacting with miR-182 and low level of GAS5 correlates with poor outcomes [26]. lncRNA GALH promotes HCC metastasis via epigenetically regulating Gankyrin and acts as an independent unfavorable prognostic indicator [27]. In this study, we focused on the newly identified lncRNA NKILA, evaluated the clinicopathological significance of NKILA in HCC patients and investigated the function and mechanism of NKILA on HCC cell biological behavior.…”
Section: Discussionmentioning
confidence: 99%
“…Histone methylation and DNA methylation, as important epigenetic modification manners, are involved in modulating the expression of numerous cancer-related genes [48,49]. For instance, a recent study revealed that linc-GALH (Gankyrin associated lincRNA in hepatocellular carcinoma), which might be a new biomarker for judging HCC metastasis, could promote the degradation of DNMT1 (DNA methyltransferase 1) by enhancing the ubiquitination and expression of Gankyrin (standard nomenclature is PSMD10) by lowering the methylation state in HCC [18]. Considerable evidence suggests that the EMT (epithelial-mesenchymal transition) is responsible for the metastasis and recurrence of tumors, including HCC.…”
Section: Lncrnas As Novel Regulators In Hcc Metastasismentioning
confidence: 99%
“…LncRNA PTTG3P (pituitary tumor-transforming 3, pseudogene) promotes the growth and metastasis of HCC by up-regulating PTTG1 and activating PI3K/AKT signaling [65]. The lncRNA-AWPPH linc-GALH, which can promote the metastasis of HCC, is also involved in the regulation of AKT signaling pathway [18,35]. Furthermore, Linc00974 promotes the proliferation and metastasis via interacting with KRT19 (Keratin 19) in HCC.…”
Section: Pathways Controlled By Lncrnas In Hcc Metastasismentioning
confidence: 99%